2021
DOI: 10.3390/bioengineering8070097
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Nanocellulose Scaffolds as a Cancer Cell Culture Model System

Abstract: Current conventional cancer drug screening models based on two-dimensional (2D) cell culture have several flaws and there is a large need of more in vivo mimicking preclinical drug screening platforms. The microenvironment is crucial for the cells to adapt relevant in vivo characteristics and here we introduce a new cell culture system based on three-dimensional (3D) printed scaffolds using cellulose nanofibrils (CNF) pre-treated with 2,2,6,6-tetramethylpyperidine-1-oxyl (TEMPO) as the structural material comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…MDA-MB-231 cells were seeded onto a bioprinted polylactic acid scaffold, and subsequently, the potential of the construct to support the expansion of the cancer stem cell niche was confirmed by the increased activity of aldehyde dehydrogenase. An upregulation of stemness marker CD44 was also reported on T47D and MCF7 cell lines cultured on a 2,2,6,6-tetramethylpyperidine-1-oxyl pre-treated cellulose nanofiber bioprinted scaffold [81]. Furthermore, the cells in that experiment have shown an increase in the expression of VIM, a marker of migration.…”
Section: Breast Cancersupporting
confidence: 58%
“…MDA-MB-231 cells were seeded onto a bioprinted polylactic acid scaffold, and subsequently, the potential of the construct to support the expansion of the cancer stem cell niche was confirmed by the increased activity of aldehyde dehydrogenase. An upregulation of stemness marker CD44 was also reported on T47D and MCF7 cell lines cultured on a 2,2,6,6-tetramethylpyperidine-1-oxyl pre-treated cellulose nanofiber bioprinted scaffold [81]. Furthermore, the cells in that experiment have shown an increase in the expression of VIM, a marker of migration.…”
Section: Breast Cancersupporting
confidence: 58%
“…Cellulosic nanomaterials, bacterial nanocellulose, cellulose nanofibers, and cellulose nanocrystals, have also drawn significant attention due to their biocompatibility, strong mechanical properties, high capacity for chemical modification, and so on [ 10 ]. Rosendahl et al [ 11 ] developed a nanocellulose-based bioink using carboxylated cellulose nanofibrils. However, in vivo biodegradability remains a major challenge since the human body lacks the enzymes which can breakdown cellulosic materials [ 10 ].…”
mentioning
confidence: 99%
“…It is worth mentioning that bioprinting has also been used for generating 3D tissue/organ models for other biomedical applications besides tissue engineering and regenerative medicine applications. For example, a bioprinted 3D cancer cell model has been developed for anti-cancer drug screening [ 11 ]. Interestingly, a 3D hydrogel-based in vitro tumor–stromal model has been produced, which recapitulates the angiogenic switch [ 22 ].…”
mentioning
confidence: 99%
“…Research on cancer, one of the most abundant diseases worldwide, would benefit from developing relevant tissue-mimicking micro-environments in order to test new drug candidates. Rosendahl et al [ 12 ] reported on an extensive study, including gene expression analysis, and showed the effect of 3D printed TEMPO nanocellulose scaffolds on cancer cells, as a step to develop novel tumor model systems. The analysis demonstrated that 3D printed nanocellulose scaffolds induced cancer stem cell characteristics on both genetic and cellular levels [ 12 ].…”
mentioning
confidence: 99%
“…Rosendahl et al [ 12 ] reported on an extensive study, including gene expression analysis, and showed the effect of 3D printed TEMPO nanocellulose scaffolds on cancer cells, as a step to develop novel tumor model systems. The analysis demonstrated that 3D printed nanocellulose scaffolds induced cancer stem cell characteristics on both genetic and cellular levels [ 12 ]. In addition, a heterogenous cell population was revealed, growing in multiple layers mimicking the in vivo situation in contrast to conventional 2D cell cultures where cells grow in a monolayer with a homogeneous cell population.…”
mentioning
confidence: 99%